Análise da produção científica em gestão do conhecimento: estratégias metodológicas e estratégias organizacionais - Duarte, Emeide Nobrega (2014)
The preoccupation with the scientific production has increased and it has stimulated the research of researches in several knowledge areas, including Administration. As this study is inserted in this context it aims to analyze the scientific production on Knowledge Management, which is reported on the Annals of National Association in Post Graduate Administration Meeting in the period from 1997 to 2002. It tries to characterize and analysis the scientific the tendencies of praxis related to general aspects of scientific production and related to methodological strategic dimensions as well as organizational strategic dimensions. The sample of the document in analysis was intentional and focused on Knowledge Management in the perspective of the organizations which were explicitly declared in the articles. These data were analysed quantitative and qualitative by using the technique of content analysis corresponding to the following variables / categories: a) concerning general aspects: evolution of the scientific production approaches to the theme, representative and importance of the theme in the document, authors concerning sex and geographical procedure, format and contents of the abstracts; b) concerning methodological strategic dimensions: delineation of the research, format of the texts, nature of the research, instruments of research; c) concerning organizational strategic dimensions: focus on people, on structure, on organizational culture, on relationship with external ambient and on technology and information systems. The approach of the adopted content analysis of data was a mixed type for the elaboration of the corpus of the categories. The results obtained appoint to favourable and unfavourable elements regarding the knowledge in the organizations, reveal omissions and suggestions for a future research as well as unveil the challenges in the Knowledge Management. The analysis and discussions carried out lead to conclude that this theme is an emerging stage of expansion and reflections about its praxis trying to find ways that shall be solved by specifics and deep scientific investigations.